Effects of acute nitrate supplementation against placebo on the physical performance of athletes in a time trial test: Systematic review and meta-analysis - Silva, W. T.; Marchado, P. G.; Mesquita, V. S. P. A.; Andrade, E. F.; Lima, R. R.; Pereira, L. J. (Science & Sports, 2023)
Objective To evaluate the effects of acute nitrate supplementation on the performance of athletes in a time trial test. News Nitrate supplementation has been used by elite athletes as an ergogenic tool. Most studies investigate the effects of chronic nitrate supplementation. However, there is no consensus on whether nitrate can improve the performance of athletes after acute ingestion. Prospects and projects This study is a systematic review and meta-analysis which evaluated the available evidence on the effects of acute nitrate supplementation on the performance of athletes in a time trial test. From 137 articles retrieved, seventeen studies were eligible for qualitative and quantitative syntheses. Conclusion The time in the against-the-clock test of supplemented athletes was lower compared to the placebo group (t2 = 135.59; P < 0.18; 95% CI of -37.23, -16.61). The acute use of beetroot juice significantly reduced the cyclists` time by 28.46 seconds (t2 = 111.06; P = 0.21; 95% CI of -39.01, -17.90). In general, the studies showed a low to uncertain risk of bias by the Cochrane tool, despite not clearly reporting the blinding of the outcome evaluators and randomization/allocation concealment procedures.